THE MEDIATING ROLE OF STUDENT SATISFACTION IN THE RELATIONSHIP OF EDUCATIONAL SERVICE QUALITY TO STUDENT RETENTION IN HIGHER EDUCATION - Endi Sarwoko; Teofilus; Erma Fina Terusia (Universitas Muhammadiyah Bengkulu, 2025)
This study focuses on the importance of service quality in enhancing student satisfaction and retention in higher education, with the Management Department of the Faculty of Economics and Business at Ciputra University as the research subject. The objective of this study is to analyze the impact of service quality on student satisfaction and retention. The theoretical framework underpinning this research is the SERVQUAL model, which measures service quality through the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. A quantitative approach is employed, targeting a population of 500 students from the 2022-2023 academic year, with a sample size of 217 respondents determined using the Krejcie and Morgan table. The research instrument consists of 40 indicators adapted from relevant journals, utilizing a five-point Likert scale to measure service quality, student satisfaction, and retention. Data analysis was conducted using Partial Least Square (PLS) with the aid of SmartPLS software, allowing for simultaneous evaluation of both the measurement and structural models. The findings of this study are expected to provide valuable insights for department management to enhance service quality and, consequently, improve student satisfaction and retention at Ciputra University.